Cultural Identity in the Shackles of Modernization: The Case of Mentawai Indigenous Peoples - Ade Irwandi; Rifki Taufik (Jurnal Sosiologi Andalas, 2023)
This paper examines the shackles of cultural identity in the new flow of the times. Mentawai people as a community group have a local identity as a characteristic of an ethnic group. However, the attraction between local culture and the pace of modernization is getting stronger, where the influence of development hegemony and policies conflict with the cultural identity of the Mentawai people. So, it raises the chaos that is still ongoing until now. Through literature study and critical anthropology view, it shows that human has the potential to create creativity and self-adjustment. However, Mentawai people are limited and suppressed by social factors and conditions, and exploited by the 'authorities'. This means that the reality of being Mentawai people is not created by nature but by humans, namely humans who have the power to 'manipulate conditions' and patent meanings that suit their minds that are full of conflict, illusion, and distortion. Mentawai people are in a 'false consciousness' that modernization helps them see the world better and have consciously stuttered (cultural backwardness) from that objective condition. Culture is deliberately clashed with the pace of modernization in various elements of life. However, Mentawai people are not rigid and make adjustments from the politically charged situation that makes them marginalized, exploited, and subordinated. Cultural tactics (cultural meaning) to follow the pace of modernization are used. Modernization and globalization are considered 'interaction spaces' in which there is a contestation arena of various elements of human life.